Traumatic periapical lesion only identified through cone beam computed tomography: A case report - Cosme-Silva, Leopoldo; Marcos, Ana Flavia Oliveira; Ferreira, Julia Fernandes; Gomes Filho, João Eduardo [UNESP]; Viola, Naiana Viana (My University, 2017)
This case report describes the diagnosis of a traumatic periapical lesion, caused by parafunctional habits (bruxism) and associated with bone rarefaction, that had not been identified by periapical radiography. Slight edema was observed clinically at the apical region of the maxillary left canine; however, the tooth demonstrated only physiologic mobility, and the results of a pulpal sensitivity test were inconclusive. A cone beam computed tomogram (CBCT) showed the presence of a periapical lesion. After preparation of the root canal, intracanal medication (calcium hydroxide and paramonochlorophenol) was placed and changed once a month for 2 months. After 60 days (at the time of the second medication change), the edema at the apical region was no longer visible. The root canal was filled, and CBCTs obtained 30 days and 24 months after completion of treatment showed that the lesion had regressed with bone repair. Although it is an expensive procedure, CBCT is important in the examination and diagnosis of periapical lesions that may not be seen in periapical radiographs.
Keywords: Computed tomography; Diagnosis; Endodontics; Root canal therapy; Tooth injuries